Evaluasi Desain Pembelajaran Sejarah Kebudayaan Islam di MTs Tarbiyah Islamiyah Kedemangan Muaro Jambi - Thoiroh; Munandar, Aris (El-Idare, 2024)
This research aims to evaluate the learning design of Islamic cultural history at MTs Tarbiyah Islamiyah Kedemangan Muaro Jambi. The method used in this research is descriptive quantitative, with data collection techniques through questionnaires distributed to 38 respondents consisting of grade IX studeat MTs Tarbiyah Islamiyah Kedemangan Muaro Jambi. Evaluations are carried out to assess the effectiveness of the teaching methods used, students' understanding of the material, as well as the obstacles faced in the learning process. The results of the research show that the learning design implemented is quite good, but there are still several aspects that need to be improved, such as the use of appropriate learning media. more variety and increased student involvement in the learning process.